Assessment of oil and gas geopolitical influence - Gu, Mengchen; Wang, Limao (Journal of geographical sciences, 2015)
This paper investigated several stages in the formation of the geopolitical influence of oil and gas, including the basis of its gestation, the means of transformation, and the formation and exercise of power. Based on this theoretical framework, a system for assessing the geopolitical influence of oil and gas was developed. This system is comprised of 13 indicators, each with its own method of measurement. Then 21 representative oil and gas importing, exporting, and transit countries were se- lected as assessment subjects. A quantitative assessment of the geopolitical influence of oil and gas in the selected countries was carried out using the proposed indicators, and factor analysis was used to obtain the main factors of these indicators and the composite score of each country. The empirical results showed that the 13 indicators could be summarized into five main factors, in the order of contribution rate, specifically comprehensive national strength, energy, transportation, risk, and geopoli- tics, each with its own variance contribution rate. Results of the assessment indicated that the selected countries could be classified into five categories in terms of oil and gas geopolitical influence： strong, relatively strong, moderate, relatively weak, and weak.